مقيد ات الاسم وأثرها في توجيه دلالة المعنى قراءة في نماذج مختارة من صحيح مسلم (Comprehensive Journal of Science, 2026)
Nominal modifiers in the Arabic language are considered decisive tools for understanding the relationship between the noun and the predicate, as well as for controlling its meaning at both the syntactic and semantic levels. In the Prophetic Hadith, these modifiers appear clearly in a variety of structures, including prepositions, the definite article (al-), copular and defective verbs, pronouns, and other restrictive elements, where syntactic functions intersect with semantic, stylistic, and pragmatic functions to produce texts that are brief in form yet rich in meaning.This study highlights selected texts from Sahih Muslim with the aim of analyzing some of these modifiers and establishing a link between the literature of traditional Arabic grammar and contemporary pragmatic linguistics.